Chapter Il socialismo europeo, Delors e il Trattato di Maastricht - GUASCONI, MARIA ELEONORA (Studi e saggi, 2023)
The essay highlights the role played by Trentin in the dialogue with the social partners, which was promoted by the President of the European Commission Jacques Delors with the Val Duchesse talks. It analyzes, in particular, the editing of the social protocol in Maastricht Treaty in 1992, and reflects on the consequences of this collaboration at the national level: his commitment to the Europeanization of CGIL and to the Italian adherence to the parameters set by the Maastricht Treaty. In particular, the agreement reached on the 23rd July 1993, still testifies to the fundamental contribution made by the three unions and, in the case of CGIL by Bruno Trentin, to the anchoring of Italy to the process of European integration and to Euro, and which were the outcomes of Trentin and Delors' collaboration.